Quality evaluation of color and texture of the Dabai fruit (Canarium odontophyllum Miq.) at different temperatures and times of blanching - Shamsudin, Rosnah; Ariffin, Siti Hajar; Zainol, Wan Nor Zanariah; Azmi, Nazatul Shima; Abdul Halim, Arinah Adila (UPM Press, 2022)
The Dabai fruit (Canarium odontophyllum Miq.) is seasonal in Sarawak. The flesh is often blanched in hot or lukewarm water to make it creamier and softer before being served as a snack or side dish. The fruit was blanched at temperatures ranging from 60°C to 100°C, with 10°C increments, for up to 10 minutes, whereby the quality changes in color and texture were investigated. Notably, the L parameter has remained unchanged during the blanching process, indicating that the dabai fruit’s dark color is retained. The parameters a*, b*, chroma (C), and total color difference (TCD), on the other hand, have increased significantly as the temperature and time of blanching are increased. However, the change in firmness was not substantial due to the slight variations in firmness as the temperature and time increased. From these findings, it can be inferred that the temperature and duration of blanching have significantly changed the dabai fruit’s color except for the firmness of the fruit. These findings would be useful in designing thermal processes and related calculations for the dabai fruit.